2020
DOI: 10.1080/00365513.2020.1742369
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors of the PD-1/PD-L1-axis in non-small cell lung cancer: promise, controversies and ambiguities in the novel treatment paradigm

Abstract: Immune checkpoint inhibitors (ICIs) have received much attention not least for melanoma since the award of the Nobel prize in 2018. Here, we review the current state of knowledge about the use of these monoclonal antibodies (mAbs) in non-small cell lung cancer (NSCLC). These drugs have generally been conditionally approved on limited early data and there are few long-term follow-up data from randomized clinical trials. The effect observed for NSCLC thus far is, on average, moderately better than that obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…With regards to the association between thyroid dysfunction and the survival outcome in patients with cancer who received PD-1 inhibitors, a previous study revealed that patients with cancer who were treated with pembrolizumab and developed thyroid dysfunction exhibited a higher median OS than those without thyroid dysfunction (40 months vs. 14 months) (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the association between thyroid dysfunction and the survival outcome in patients with cancer who received PD-1 inhibitors, a previous study revealed that patients with cancer who were treated with pembrolizumab and developed thyroid dysfunction exhibited a higher median OS than those without thyroid dysfunction (40 months vs. 14 months) (21).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the association between thyroid dysfunction and the survival outcome in patients with cancer who received PD-1 inhibitors, a previous study revealed that patients with cancer who were treated with pembrolizumab and developed thyroid dysfunction exhibited a higher median OS than those without thyroid dysfunction (40 months vs. 14 months) ( 21 ). Another study indicated that patients with NSCLC and thyroid dysfunction who received PD-1 inhibitors exhibited significantly higher OS and PFS than those without thyroid dysfunction ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Distinctive expression pattern of PD-L1 has been shown on different tumor cells and related TME, such as malignant melanoma, NSCLC, ovarian cancer, bladder cancer, breast cancer, renal cell carcinoma, and gastric cancer. [23][24][25][26][27][28][29] In contrast, the difference in efficacy of the PD-1/PD-L1 blockade response might not associate with the expression level of PD-L1. 30 FDA approved membrane staining immunohistochemistry (IHC) assays, including PD-L1 IHC 28-8 phar-mDx, PD-L1 IHC 22C3 pharmDx, VENTANA PD-L1 SP263, and VENTANA PD-L1 SP142 for determining the PD-L1 expression level in different tumors.…”
Section: Pd-l1 As a Biomarker For Cancer Immunotherapymentioning
confidence: 98%
“…These drugs have now set new standards to the point that ICIs evolved to become first-line treatment [9][10][11][12][13][14] . However, for unknown reasons, an estimated half of the NSCLC patients are refractory to this new modality and the majority become resistant after an initial response [15][16][17][18] .…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%